PENGARUH ANGULASI PEMBENTUKAN DAN AKHIRAN PREPARASI TERHADAP KEAKURATAN TEPI DAN INTERNAL OVERLEI RESIN KOMPOSIT 3D PRINTING - Sinatra, Talisa Claudiary; Dwisaptarini, Ade Prijanti; Stefani, Rosita; Eddy, Eddy (Poltekkes Kemenkes Bandung, 2025)
Marginal and internal fit accuracy are critical factors for the success of indirect restorations. With advancements in Liquid Crystal Display (LCD)-based 3D printing technology, this study evaluates the effects of build angle and preparation margin design on the accuracy of 3D-printed resin composite overlays. This study aims to analyze differences in the marginal and internal fit accuracy of 3D-printed resin composite overlays based on build angle (150° and 180°) and preparation margin designs (shoulder and functional cusp bevel). This experimental study used 40 overlay samples divided into four groups based on combinations of build angle and preparation margin design. Marginal and internal fit accuracy was assessed using the silicone weight technique, and using the silicone replica technique with a digital optical microscope. Data were statistically analyzed using Two-way ANOVA and Post Hoc Tukey tests. Build angle statistically influenced both marginal and internal fit accuracy (p<0.05). The 180° angulation group showed better results compared to 150°. Preparation margin design did not significantly affect internal fit accuracy, although the functional cusp bevel design exhibited larger marginal gaps than the shoulder design in specific measurements. Conclusion: The build angle affects the marginal and internal fit accuracy for 3D-printed resin composite overlays using the LCD method and 180° yields better marginal and internal fit accuracy. Preparation margin design did not significantly affect internal fit accuracy.